Co-mobility in the digital age: Changing technologies, and the affects of presence in journeying 'with' others. Issue 3 (2nd September 2021) - Hughes, Ainsley; Mee, Kathy
ABSTRACT: Co-presence, proximity, and moving with other people, have long been recognised as important factors in our decision-making and performances of everyday wayfinding. Such arguments have roots in the work of sociologist Erving Goffman, whose concept of the "mobile with" has been widely used to articulate the fluid conglomerations of bodies who come to move together. This paper pushes Goffman's idea of the "mobile with" into the digital age, opening our field of view to an expanded understanding of "co-mobility". Drawing on the autoethnographic accounts of one of our authors, we illustrate that with the advent of new technologies, bodies are constantly and simultaneously connected to near and distant others, and known and unknown travel companions. These complex techno-communities take form in two key ways: via the sensory and haptic forms of communication required in using technological devices, and the virtual presence afforded by the ability to enact these communications across time and space. Using affect as a lens of analysis, this paper illustrates that sharing co-mobile experiences with near and distant others evokes a particular style of presencing. Importantly, the various affects of presence are called into focus in intense moments, with implications for how people perform their mobilities in the moment, and the lingering emotions they carry in contemplating future mobilities.